TEACHING ENGLISH IN PRIMARY SCHOOLS - Scientientific supervisor: Fayzullayeva Dilnoza Student: Gulimboyeva Farangiz Student of, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In this article you may see the lack of English language teachers in primary schools makes teaching English to young learners a challenge. Because of this, primary school instructors are required to teach English in the second, third, and fourth grades even though they lack the necessary educational background and English proficiency. By taking into account elementary school teachers' and English language teachers' shortages. This study looks at the difficulties these primary school teachers had, how they were resolved, and how the course on teaching English to children affected the ideas of prospective teachers. In order to respond to the research questions and analyze the data, which were acquired through unstructured interviews, a cross-sectional qualitative research strategy was adopted in this study.